A Review on Heavy Metal Pollution of Agricultural Land Soil in the Yangtze River Delta and Relevant Pollution Control Strategy - Gan Tingting (《中国工程科学》杂志社, 2021)
The Yangtze River Delta is an important industrial and agricultural production base in China. It is significant to pay attention to the heavy metal pollution of agricultural land in the Yangtze River Delta for promoting the healthy development of social economy and for ensuring the safety of ecological environment in China. In this paper, the accumulation and pollution status of typical heavy metals in the agricultural land soil in different regions of the Yangtze River Delta were comprehensively analyzed and the main reasons for the pollution were systematically discussed, according to the heavy metal content data reported in relevant literatures published over the past 20 years. The analysis revealed that due to industrial “three wastes” emissions, transportation, and the extensive use of fertilizers, pesticides, and agricultural films, Cd accumulation and pollution in the agricultural land soil of the entire Yangtze River Delta is the most serious, followed by Cu, Hg and Pb pollution; specifically, Taizhou (in Zhejiang Province) has a compound pollution problem of Cd, Hg, and Cu while Tongling (in Anhui Province) has a compound pollution problem of Cd, Pb, and Cu. To meet the urgent need for the prevention and control of heavy metal pollution in the Yangtze River Delta and considering the main causes of pollution, some suggestions were proposed, including source control, rapid and dynamic monitoring, hierarchical management of agricultural land, research and development of new technologies for soil remediation, and legislation on prevention and control of agricultural land soil pollution. It is hoped that this research can provide a reference for improving the soil ecological environment in the Yangtze River Delta and promoting the sustainable development of a high-quality and efficient agriculture.